Penerapan Teori Behavioristik Classical Conditioning Oleh I.P Pavlov dalam Pembelajaran IPA Siswa Kelas 5 Sekolah Dasar - Sukanadi, Ni Wayan Sri; Suarni, Ni Ketut; Margunayasa, I Gede (Universitas Batanghari Jambi, 2024)
This research was conducted in response to a number of difficulties faced as well as the low level of interest in learning from grade 5 elementary school students in the context of science learning. This study focuses on the science learning ability of grade 5 students in elementary schools in response to the results of PISA 2018, Indonesian Education Report Card Data, and AKM Scores which show the low level of students' science literacy skills. Using the Nonequivalent Pretest Posttest Control Group design, experimental research was conducted to evaluate the impact of the application of Behavioristic Classical Conditioning Theory by I.P Pavlov in science learning. Class V students were divided into experimental and control groups with the Cluster Random Sampling Technique. The test method was used to collect science learning ability data, and the data analysis used the Polled Variance T test due to homogeneous data variance. The results showed a significant difference in science learning ability between the group that applied the Behavioristic Classical Conditioning Theory and the control group. The implications of this research provide a solid foundation for designing effective learning strategies in the future, focusing on curriculum development and learning approaches that can enhance students' understanding and interest in learning. As an effort to improve the quality of science learning in elementary schools, this research provides significant conceptual and applicative contributions.